The Development of Pop Up Book Learning Media for Grade III Learners in Elementary School - Proklamasari, Agus Setyowati Devita; Atiqoh, Atiqoh; Hartono, Hartono (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study aims to analyse Pop Up Book Learning Media for Grade III Learners in Elementary Schools. This Pop Up Book learning media was developed with the ADDIE Model (Analyze, Design, Develop, Implement, Evaluate). The subjects of this development research are third grade students of SDN Ketegan 3 Taman Sidoarjo. The research instruments used to collect data in this development research include (1) questionnaires, which consist of validation questionnaires for material experts, media experts, design experts, practicality test questionnaires for small group tests and small group tests, (2) practicality test questionnaires for small group tests and field tests, and (3) student response questionnaires for field tests and large group tests. The results of learning media research on the quality of Pop Up Book media, determined by material expert validators with a total score of 49 with an average media validation result of 4.08 so that it has reached the ‘Very Valid’ category. reached the ‘Very Valid’ category. In the media expert validator, the number of scores is 57 with an average media validation result of 3.8. The average acquisition of the number of scores has reached the ‘Very Feasible’ category and the design expert validator has a total score of 59 with an average media validation result of 4.53. The average acquisition of the number of scores has reached the category ‘Very Feasible’.